IMPLEMENTASI MEDIA PEMBELAJARAN AUDIO VISUAL UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PAI DI MTS DAARUL IHYA DESA KURIPAN, KECAMATAN CISEENG, KABUPATEN BOGOR - Ibnu Rozaq, Arip Rahmat; Khoiriyah, Binti; Kabibuloh, Nur (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2023)
The method of learning PAI is usually only with the lecture method and does not utilize other learning media, so that learning becomes less effective and interesting and even makes students bored and boring. This research focuses on the goal of increasing students' interest and understanding at MTS Daarul Ihya by implementing audio-visual-based Islamic religious education (PAI) learning media. This research uses descriptive qualitative methods with data collection techniques through interviews, observation, and documentation. The data analysis uses interactive which consists of data collection, data condensation, data presentation, and conclusion drawing. To test the validity of the data, researchers used source triangulation. The results showed that the use of audio visual media as a learning medium can increase students' interest and enthusiasm and understanding of Islamic religious education subjects, then the use of audio visual-based learning media can also increase the effectiveness of teachers in delivering material to students.